Mutant IDH1 promotes glioma formation in vivo - Philip, B; Yu, DX; Silvis, MR; Shin, CH; Robinson, JP; Robinson, GL; Welker, AE; Angel, SN; Tripp, SR; Sonnen, JA; VanBrocklin, MW; Gibbons, RJ; et al. (Elsevier, 2018)
Isocitrate dehydrogenase 1 (IDH1) is the most commonly mutated gene in grade II-III glioma and secondary glioblastoma (GBM). A causal role for IDH1R132H in gliomagenesis has been proposed, but functional validation in vivo has not been demonstrated. In this study, we assessed the role of IDH1R132H in glioma development in the context of clinically relevant cooperating genetic alterations in vitro and in vivo. Immortal astrocytes expressing IDH1R132H exhibited elevated (R)-2-hydroxyglutarate levels, reduced NADPH, increased proliferation, and anchorage-independent growth. Although not sufficient on its own, IDH1R132H cooperated with PDGFA and loss of Cdkn2a, Atrx, and Pten to promote glioma development in vivo. These tumors resembled proneural human mutant IDH1 GBM genetically, histologically, and functionally. Our findings support the hypothesis that IDH1R132H promotes glioma development. This model enhances our understanding of the biology of IDH1R132H-driven gliomas and facilitates testing of therapeutic strategies designed to combat this deadly disease.